Methoxy poly (ethylene glycol)-b-poly (δ-valerolactone) copolymeric micelles for improved skin delivery of ketoconazole. Issue 1 (2nd January 2017) - Deng, Peizong; Teng, Fangfang; Zhou, Feilong; Song, Zhimei; Meng, Ning; Feng, Runliang
Abstract: Ketoconazole is a broad spectrum imidazole antifungal drug. For the treatment of superficial fungal infections with ketoconazole, it needs to be permeated to deep skin layers. In order to develop topical formulation of ketoconazole for improving its skin deposition and water-solubility, ketoconazole-loaded methoxy poly (ethylene glycol)-b-poly (δ-valerolactone) micelles were developed through thin-film hydration method. Particle size, drug loading capacity, infrared spectrum and X-ray diffraction of drug-loaded micelles were characterized. The optimal drug formulation was selected for skin delivery and deposition investigation performed by use of mice skin, and its in vitro release and antifungal activity were also investigated. Penetration and distribution in the skin were also visualized using fluorescein-loaded micelles and fluorescence microscopy. The drug-loaded micelles were obtained with encapsulation efficiency of 86.39% and particle diameter of about 12 nm. The micelles made ketoconazole aqueous solubility increase to 86-fold higher than crude one. Ketoconazole-loaded micelles showed no skin permeation of ketoconazole, obviously enhance skin deposition and demonstrated similar antifungal activity as compared with marketed ketoconazole cream. Fluorescein-loaded micelles displayed higher skin deposition than fluorescein water solution. These results demonstrate that the MPEG-PVL micelle is a potential delivery system for ketoconazole in the field of skin delivery.